Organizational Goals and Expected Behavior among American, Japanese and Korean Managers—A Comparative Study - England, George W.; Lee, Raymond (Academy of Management Journal, 1971)
Empirical evidence is presented about organizational goals as viewed by samples of over 1,600 American, Japanese, and Korean managers. Comparative analyses of organizational goal perceptions and expected organizational behavior suggest that cultural factors have an important impact on managerial values as expressed in organizational goals. Country differences and similarities found in the perceptions of goals are generally in accord with the managerial ideology, economic development, and social facts of the three countries.